Development and analysis of VAWT offgrid in ducting system - Irni Hamiza Hamzah; M. H. Roslan; A. A. Malik; N. W. M. Saad; A. F. A. Rahim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Horizontal Axis Wind Turbine (HAWT) had been widely used in Malaysia, however, research concluded that the power produced is still low which approximately 0.02% from the wind turbine input is. The average wind speed in Penang, Malaysia, is recorded between 1.0 m/s to 2.5 m/s whereby to produce 2.7 kW of power by HAWT, 12.0 m/s of average wind speed is needed. Therefore, the main objective in this project is to develop and analyse the suitability on the Vertical Axis Wind Turbine (VAWT) to be used for power generation with the wind speed in between 0.5 m/s to 3.0 m/s. Ducting system is chosen rather than the open air since commercial buildings used Heat Ventilation Air Conditioning (HVAC) system. Arduino microcontroller and LabVIEW is used as interfaced to setup two types of sensors that is temperature sensor and anemometer.